Supply Chain Performance Determinants Model in Furniture SMIs - Widiartanto Widiartanto; Fendy Eko Wahyudi; Amni Zarkasyi Rahman (Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
Research to find the determinants of company performance has long been a field of strategic management studies. Many researchers discover why companies do better than others. In recent years, supply chain terminology has begun to emerge, in which a supply chain is a unit that transforms raw materials into finished products through a gradual, parallel, and/or networked structure partially or simultaneously. This study focuses on explaining supply chain performance in order fulfillment and delivery of required products to customers, with the market turbulence as a moderating variable that strengthens or weakens the relationship between the culture of competitiveness and knowledge development on supply chain performance. The research was conducted in Jepara Regency by taking samples of the Wood Furniture UKM in the Tahunan Village, Tahunan District with quantitative approach. The population in this study are all wood furniture business owners in the Tahunan Village, Tahunan District, Jepara Regency. The data are collected through a cluster random sampling technique with a probability proportional to size sampling method, with a research sample of 65 Wood Furniture UKM. The results show that the culture of competitiveness and knowledge development has a positive and significant effect on supply chain performance, either partially or simultaneously. Meanwhile, the market turbulence is only a potential moderating variable in the relationship between the culture of competitiveness and knowledge development on supply chain performance. Suggestions that can be given include sharing data and information as well as developing a shared understanding of supply chain management information that needs to be done among members of the Wood Furniture UKM Association in the Tahunan Village.